2021
DOI: 10.1111/jace.17797
|View full text |Cite
|
Sign up to set email alerts
|

Low thermal conductivity of SrTiO3−LaTiO3 and SrTiO3−SrNbO3 thermoelectric oxide solid solutions

Abstract: Electron-doped SrTiO 3 has been attracting attention as oxide thermoelectric materials, which can convert wasted heat into electricity. The power factor of the electrondoped SrTiO 3 , including SrTiO 3 -LaTiO 3 and SrTiO 3 -SrNbO 3 solid solutions, has been clarified. However, their thermal conductivity (κ) has not been clearly identified thus far. Only a high κ (>12 W m −1 K −1 ) has been assumed from the electron contribution based on Wiedemann-Franz law. Here, we show that the κ of the electrondoped SrTiO 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
(151 reference statements)
3
4
0
Order By: Relevance
“…Similar behavior was also reported by other researchers both in La/Nb doped and oxygen-deficient BaTiO 3 , where a small polaron hopping of conduction mechanism was deduced [31][32][33][34]. In contrast, the μ Hall of STNO system is limited by large polarons [14]. The lattice distortion in BTNO will bring a much stronger trapping potential for carriers, resulting in the formation of small polarons.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Similar behavior was also reported by other researchers both in La/Nb doped and oxygen-deficient BaTiO 3 , where a small polaron hopping of conduction mechanism was deduced [31][32][33][34]. In contrast, the μ Hall of STNO system is limited by large polarons [14]. The lattice distortion in BTNO will bring a much stronger trapping potential for carriers, resulting in the formation of small polarons.…”
Section: Resultssupporting
confidence: 87%
“…However, comparing κ ele and κ, it could be found that κ is much lower than κ ele in BTNO at x0.6, even though the lattice structure is isotropic along the in-plane and cross-plane directions. A similar phenomenon was also found in STNO system [14]. This may be due to the different measurement directions of σ and κ, which results in a different scattering rate for electrons and phonons.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Orthorhombic SrCeO 3 with good damage tolerance, proton conductivity, high coefficient of thermal expansion, and phase stability at 1200°C, has been a potential material for thermal barrier coatings and solid oxide fuel cells [8,9] . Due to a lattice distortion that could enhance the phonon and electron scattering, a solid solution, SrTiO 3 -LaTiO 3 , has a low thermal conductivity [10] . In SrTiO 3, with periodically twinning boundaries, the thermal conductivity can be decreased, as a result of the decrease in phonon mean free path [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Oxides such as ZnO, In 2 O 3 , CaMnO 3 , and SrTiO 3 are chemically and thermally stable in air and the preparation process is easy and eco‐friendly, which have been indicated as promising candidates for high‐temperature TE applications. [ 25–34 ] However, the thermoelectric performance of those oxide semiconductors is much lower than that of alloys, owing to low carrier mobility and high thermal conductivity resulting from high electronegativity and remarkable ionic contribution to chemical bonding of oxygen atoms. Differently, layered oxygen‐containing compounds such as Na x CoO 2 and Ca 3 Co 4 O 9 have high carrier mobility and anisotropic thermoelectric properties, and layered oxyselenides such as Bi 2 O 2 Se and BiCuSeO also have strong anharmonicity and extremely low thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%